A statistical perspective on running with prosthetic lower-limbs: An advantage or disadvantage? - Hassani, H.; Ghodsi, M.; Shadi, M.; Noroozi, S.; Dyer, B. (Sports, 2014)
Technological developments have led to the increased use of carbon fiber and prosthetic lower-limbs in running events at the Paralympic Games. This study aims to exploit a series of statistical techniques in order to prepare a response to the vital question of whether utilizing prosthetic feet can affect an athletes ability when running competitively at the Paralympics Games by comparing both within and between different classifications. The study also considers the differences between running on biological limbs and prosthetic lower-limbs from a mechanical point of view. The results from the male 100 m, 200 m and 400 m at the 2012 London Paralympic Games have been the source of this investigation. The investigation provides statistical evidence to propose that the number of prosthetic limbs used and the structure of such limbs have a significant impact on the outcome of track events at the Paralympic Games.